German sculpture of the later Renaissance c. 1520 - 1580 ; art in an age of uncertainty - Smith, Jeffrey Chipps 1951- (Princeton Univ. Press, 1994)
Focusing on how sculptures adjusted to this cultural tumult, Jeffrey Chipps Smith offers the first comprehensive examination of the artistic response to the challenge of the Reformation in German lands. In so doing he exposes the years leading up to the Counter-Reformation as a period of surprising artistic vibrance